Main lobe jamming suppression via blind source separation sparse signal recovery with subarray configuration. Issue 3 (12th February 2020) - Ge, Mengmeng; Cui, Guolong; Yu, Xianxiang; Kong, Lingjiang
Abstract : The performance of the modern radar systems will degrade significantly in the presence of main lobe jamming. In this study, a new methodology is introduced to suppress multiple main lobe jammings while accomplishing the directions of arrival (DOAs) estimation of the multiple targets. Specifically, the signal model of a specific subarray configuration accounting for jamming and target signals is developed. Then, blind source separation method is utilised to separate the target and jamming signals in each subarray. Furthermore, the separated target signals of all subarrays are jointly imposed to estimate DOAs of targets through resorting to sparse signal recovery approach. Finally, numerical simulations are provided to assess the performance of the proposed algorithm exhibiting the favourable capabilities in terms of the strong main lobe jamming suppression and the DOAs estimation of multiple targets.